2021
DOI: 10.1021/acs.joc.1c02417
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Palodesangrens A and C

Abstract: Palodesangrens A and C along with the common tetracyclic core are prepared from simple benzaldehyde and acetophenone derivatives in a 10-step longest linear sequence which featured the Diels–Alder reaction forming the cyclohexene moiety, LiAlH4 isomerization, stereoselective acid-catalyzed cyclization forming the chroman moiety, regioselective iodination/vinyl Suzuki cross-coupling reaction, and ring-closing metathesis (RCM) forming the 2H-pyran-2-one. Overall, the desired palodesangrens A and C are obtained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Other investigations have shown that phenols and their ethers can act as redox tags in electrocatalytic Diels-Alder reactions and that silver Frontiers in Natural Products frontiersin.org nanoparticles can catalyze related Diels-Alder reactions involving phenolic chalcones and terpenoid dienes (Cong et al, 2008;Cong et al, 2010). When comparing biomimetic Diels-Alder reactions involving a chalcone and a 2,4disubstituted diene, it was found that the desired reactions with moderate yield require high pressures or temperatures, or strong Lewis acids (ONeill et al, 2006;Tee et al, 2016;Chai et al, 2020;Tangdenpaisal et al, 2022). However, when using enzymatic (Gao et al, 2020) or redox-active catalysts (Cong et al, 2010;Ohmura et al, 2023), nearly identical reactants can undergo the Diels-Alder reaction at room temperature or even below, demonstrating a more efficient and milder process.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations have shown that phenols and their ethers can act as redox tags in electrocatalytic Diels-Alder reactions and that silver Frontiers in Natural Products frontiersin.org nanoparticles can catalyze related Diels-Alder reactions involving phenolic chalcones and terpenoid dienes (Cong et al, 2008;Cong et al, 2010). When comparing biomimetic Diels-Alder reactions involving a chalcone and a 2,4disubstituted diene, it was found that the desired reactions with moderate yield require high pressures or temperatures, or strong Lewis acids (ONeill et al, 2006;Tee et al, 2016;Chai et al, 2020;Tangdenpaisal et al, 2022). However, when using enzymatic (Gao et al, 2020) or redox-active catalysts (Cong et al, 2010;Ohmura et al, 2023), nearly identical reactants can undergo the Diels-Alder reaction at room temperature or even below, demonstrating a more efficient and milder process.…”
Section: Discussionmentioning
confidence: 99%
“…A radical cyclization approach was explored by Parker and co-workers to gain access to natural product bisabosqual A (am Ende et al, 2013;am Ende and Parker, 2019). Substituted 1-aryl-1,3-butadienes have been evaluated in Diels-Alder strategies toward cis-fused tetrahydrobenzo[c]chromenes including epiconicol and some members of palodesangrens family of natural products (Minuti et al, 2015;Tangdenpaisal et al, 2019;Tangdenpaisal et al, 2022). A domino electrocyclic ring-opening/hetero Diels-Alder reaction of 2-prenylated 2H-pyrans, originally developed by Chizhova and Anufriev (Chizhova and Anufriev, 2000), has been employed for the synthesis of reduced versions of cannabinoids (Garcia et al, 2009), natural products benzosimuline (Riveira et al, 2016), 7-demethylnaphterpin (Murray et al, 2018), as well as others (Coleman et al, 2019;Murray et al, 2019).…”
Section: Scheme 11mentioning
confidence: 99%